EDUCATIONAL TESTING AND MEASUREMENT Classroom Application and Practice - Kubiszyn, Tom; Borich, Gary D. (Wiley, 2024)
Educational Testing & Measurement Revised and updated edition of the reader-friendly, classroom-relevant introduction to testing and assessment, designed for educators to meet today's challenges in measuring student progress. Educational Testing and Measurement, Twelfth Edition, is a revised and updated practical resource that will enhance assessment literacy to help prepare current and prospective teachers to navigate today's changing world of educational testing and assessment. It describes the classroom impact of national and key state-level policy changes that drive the ongoing changes in the usage of both teacher-made and standardized tests and assessments. Educational Testing and Measurement, Twelfth Edition presents a balanced perspective of educational testing and assessment, with a unique approach to descriptive statistics and psychometrics (validity, reliability, and fairness).